IMPLEMENTASI WEB SERVICE UNTUK PLATFORM FREELANCE DIGITAL DENGAN METODE EXTREME PROGRAMMING - Rayhanantha Akbar Putra Prasetyo; Irwan Alnarus Kautsar; Hamzah Setiawan (Jurnal Tekinkom (Teknik Informasi dan Komputer), 2024)
Freelancing has been trending for a few years lately, this kind of job industry is game-changing with many different jobs vacant. Technologies that are established further give new opportunities for freelancing jobs, moving from attending the office to working at home or on our own time services. Web service is one of the most used technologies that have been spread over many uses, it is one of the Application Programming Interface (API) branches, such as providing data and storage of data, this usability helps in many ways of software development, some application required a way to secure their data usage, efficiency on distributing data, easy use for development sustainability and maintainability. Extreme programming is a fast-paced development method that adapts with requisites on developed applications, by using this method hoping to achieve a developed web service could help freelance industries by distributing integrated freelancer data on many freelancing platforms, in in-order to help freelancing platform develop their main features or such add-ons features to help freelancer promote their services within that platform.